Impact of rli87 gene deletion on response of Listeria monocytogenes to environmental stress. Issue 1 (4th September 2014) - Kun, Xie; Qingling, Meng; Qiao, Jun; Yelong, Peng; Tianli, Liu; Cheng, Chen; Yu, Ma; Zhengxiang, Hu; Xuepeng, Cai; Chuangfu, Chen
Abstract Listeria monocytogenes (LM) is a zoonotic pathogen that widely adapts to various environments. Recent studies have found that noncoding RNAs (ncRNAs) play regulatory roles in LM responses to environmental stress. To understand the role of ncRNA rli87 in the response regulation, a rli87 deletion strain LM‐Δrli87 was constructed by homologous recombination and tested for stress responses to high temperature, low temperature, high osmotic pressure, alcohol, acidity, alkaline and oxidative environments, along with LM EGD‐e strain (control). The results showed that compared with LM EGD‐e, LM‐Δrli87 grew faster (P < 0.05) at low temperature (30 °C), high temperature (42 °C), and in alkaline condition (pH = 9), similarly (P > 0.05) in acidic and high osmatic pressure (10% NaCl) conditions. When cultured in medium containing 3.8% ethanol, the growth was not significantly different between the two strains (P > 0.05). When cultured at pH 9, they had similar growth rates in the first 5 h (P > 0.05), but the rates were significantly different after 6 h (P < 0.05). The expression of rsbV, rsbW, hpt, clpP, and ctsR was upregulated in LM‐∆rli87 compared with LM EGD‐e at pH 9, indicating that the rli87 gene regulated the expression of the five genes in alkaline environment. Our results suggest that the rli87 gene has an important regulatory role in LM's response to temperature (30 and 42 °C), alkaline stresses.